2014
DOI: 10.7860/jcdr/2014/7818.4441
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cholesteryl Ester Transfer Protein (CETP) I405v Genotype and Its Association with Lipid Fractions in Myocardial Infarction Patients: A Case Control Study

Abstract: Objectives: We determine the significant relation of HDL cholesterol and total cholesterol/HDL cholesterol between CETP I405V genotypes and activity of CETP.CETP is an essential for transfer of cholesterol ester to the liver from peripheral tissues which facilitating its transfer to TG rich VLDL. Reduction activity of CETP I405V may associate with genotypes of CETP I405V. This study is undertaken to assess the presence and impact of CETP I405V genotype in our population. Materials and Methods: In this study 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The rs100775 (CETP) variant was associated with lower levels of HDL-C levels in our study and other studies [17,18,20]. CETP is proatherogenic and promotes the transfer of cholesteryl ester from HDL-C to very low-density lipoprotein (VLDL) rich in triglycerides [22,23,24,47].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The rs100775 (CETP) variant was associated with lower levels of HDL-C levels in our study and other studies [17,18,20]. CETP is proatherogenic and promotes the transfer of cholesteryl ester from HDL-C to very low-density lipoprotein (VLDL) rich in triglycerides [22,23,24,47].…”
Section: Resultssupporting
confidence: 76%
“…However, deficiency in LIPC favors the accumulation and circulation of cholesterol-rich atherogenic particles [17]. CETP promotes the transfer of cholesteryl ester from HDL-C to very low-density lipoprotein (VLDL), which is rich in triglycerides [22,23,24]. Its deficiency is thought to be a major reason for high levels of HDL-C in Asians [23].…”
Section: Introductionmentioning
confidence: 99%
“…Among these eligible studies, 33 involved the relationship between CETP rs708272 polymorphisms and CAD ( 15 47 ). Other 37 studied five other polymorphisms in the CETP gene, and 14 of them focused on rs5882 ( 15 , 22 , 26 , 29 , 31 , 32 , 35 , 44 , 46 , 50 , 53 , 55 , 59 , 60 ), 11 on rs1800775 ( 26 , 27 , 31 , 32 , 35 , 44 , 52 , 57 60 )3 on rs4783961 ( 16 , 35 , 51 ), 3 on rs247616 ( 19 , 48 , 56 ), 2 on rs5883 ( 49 , 54 ), 2 on rs1800776 ( 44 , 60 ), and 2 on rs1532624 ( 19 , 26 ). In addition, 6 studies deviated from HWE ( 19 , 30 , 32 , 39 , 41 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-six articles involved cases with coronary stenosis ( 15 17 , 19 , 20 , 22 34 , 36 , 38 40 , 43 , 44 , 46 54 , 56 , 57 , 59 ), and 10 involved cases with myocardial infarction ( 18 , 21 , 35 , 37 , 41 , 42 , 45 , 55 , 58 , 60 ).…”
Section: Resultsmentioning
confidence: 99%
“…A few other studies have shown an association between CETP and lipid metabolism 16 33 34 . The reports from India are varied as each has looked at different CETP polymorphisms and HDL-C metabolism 35 36 . In the study by Dixit et al 36 , lipid profile analysis did not show any significant difference in distribution among genotypes of CETP polymorphism among patients and controls.…”
Section: Discussionmentioning
confidence: 99%